Eskimo Ice Cream and Kraft Dinner Goulash: The Cultural Geographies of Food in Three Cookbooks from the Northwest Territories (NWT), Canada - Christensen, Julia (Cuizine)

(untitled) (McGill University Library, 2013)
In this article, I explore three Northwest Territories (NWT) cookbooks from the 1960s. The first cookbook, a fundraiser for the Anglican Church in Inuvik, demonstrates the significance of traditional Indigenous food preparations, as well as the integration of imported recipes, adapted to draw resourcefully on northern store provisions of that time. Most, if not all, of the recipes are provided by Indigenous women. The second, published by the Daughters of the Midnight Sun in Yellowknife, is a hospital fundraiser that offers a different perspective - that of an emerging population of newcomers from elsewhere in Canada and the world. While the recipes attest to the diverse roots of settlers in a growing community, they also tell a story of exclusion: one cannot help but wonder at the lack of Indigenous representation among the recipe writers, in a community built within the traditional homelands of the Yellowknives Dene First Nation. The third, published by the Department of Indian Affairs and Northern Development, offers tips to northern “wilderness wives” on nutrition along with recipes that are often out of touch with the availability of certain ingredients in northern communities. Drawing on feminist and postcolonial theory, I critique these cookbooks: analyzing both the recipes and the positionalities of their writers, to explore how the north was imagined by three different, often opposing, perspectives; and offering insight into (persistent) colonial geographies of food and community in the NWT.